Consolidation Models at Acquisition: Purchase and Pooling of Interest Methods. - Kimmell, Dennis Lee (The Accounting Review, 1976)
Abstract Accounting students at both the beginning and advanced levels sometimes have difficulty in mastering the concept of reporting the financial position of two or more companies on a consolidated basis. The purchase method, with concepts such as goodwill and minority interest and the pooling of interest method, for which varying relationships between the total par or stated value of the shares issued by the acquirer and the total paid-in capital of the company whose shares are acquired require alternative treatments, cause many students some consternation. Often, these techniques are not mastered by students because there is too much data to be processed at one time. Students are expected to manage the numerical complexities as well as to grasp the theoretical concepts using a single illustration. To alleviate this problem, models reflecting consolidation at acquisition were developed as a means of focusing on concepts involved and have been used in the classroom setting with some success. The principal advantage of these models is that they are succinct, that is, concepts are presented in a small amount of space, in a short period of time and can be presented independently of numerical data.